Subkey generation method for symmetric - key block cryptogaphy using a chaotic map [electronic resource] - 311576 Niki Anis Ab. Karim (Skudai : Universiti Teknologi Malaysia, 2007)
Project Paper (Sarjana Muda Sains (Matematik)) - Universiti Teknologi Malaysia, 2007